Kajian Program Latihan Khidmat Negara (Kumpulan 'Hardcore') - Hajjah Mizan Adiliah Ahmad Ibrahim; Naim Hj. Ahmad; Abd Hamid Abd Murad (Universiti Sains Islam Malaysia, 2024)
This research on the National Service Training Program (Special) was conducted based on 'participant observation' method. The research was conducted at two camps; they were Akaderni Latihan Inovasi dan Motivasi (ALIM) and Burni Jati Camps. The research was conducted over three months on 130 male National Service trainees that were separated due to several factors which identified the camps as 'hard core'. The main purpose of the research is to identify the objectives of why this special program was created, trainers' difficulties, the profile of the participants' involved, participants' religious understanding, participants' development and the effectiveness of the modules. The results of the studies showed that the objectives and purpose of creating this program was not clearly defined. A majority of the trainees were 18 years of age. Most of them were immature in terms of thoughts and emotions and lead a free lifestyle, and they have low religious background and understanding. Trainees have a low education background, attained a qualification less than a Sijil Pelajaran Malaysia (SPM). Unclear tasks between the trainers, facilitators, and the administrative staff were also identified as a main problem in this program. This research has taken into consideration the various observations from the trainers, facilitators and administrative staff regarding the achievement of the program whereby they are of the opinion that the program has not succeeded in attaining its actual objectives of the program. Several suggestions are recommended here in ensuring a better program in the future such as conducting a detailed study in the selection of the trainees for this program, conducting drug, HIV and AIDS screening tests on the trainees, prohibiting the use of mobile phones (hand phones), anci prohibition 01 smoking while undergoing the programme. Immediate action has to be taken towards the weakness of the modules by creating specific modules for special camps and increase the participants7 discipline during the training.